Pengaruh Proses Observasi Magang Terhadap Motivasi Mahasiswa - Siregar, Deasy Yunita; Ismayati, Hafizah; Nur Ain Nun; Jannah, Miftahul; Aulia, Sirrul (PT. Kreasi Karya Majakata, 2023)
Preparing interns to become professional educators is the program's first priority. This includes a protracted process that begins with locating and observing a school and ends with candidates being able to stand and teach in class according to the needs and desires of their pupils. Preservice teachers need to be well-versed in four areas: 1) pedagogy, 2) professionalism, 3) social competence, and 4) personality. This study aims to shed light on how an internship programme might enhance these abilities. This study employed exploratory and descriptive approaches to analyse secondary data collected through surveys. Students in the English Language Studies major contributed data for this study. Students whose first internship was in an English language training programme were the topic of this study. As a component of Internship Programme I, learning process observation helps students develop a sense of educational identity and improves their academic competence in the classroom. Effective and responsive teaching abilities, as well as an understanding of the strategies necessary to become competent educators who can adapt to varied school situations, are the goals of this exercise, which is designed to help interns improve these talents. First language education internship programme English is a programme that seeks to enhance students' proficiency and enthusiasm for learning the English language.